واقع الابتكار الحكومي في الدول العربیة وسبل تطویره، تجربة الجزائر، الإمارات والمغرب - رولامي, عبد الحميد (Finance and Business Economies Review, 2018)
This study highlihts the reality of innovation in the governments of three Arab countris : Algeria, Morocco, and United Arab Emirates. We relied on comparing the Global Innovation Index with the Global Development Indicators of Science and Technology, We tried to know the impor e of innovation in the provision of public service and in economic development as well. As a conclusion, we have made some suggestions and recommendations that may help these governments to invest in government innovation to develop their performance.